Performances of Crypto, Market Indexes, and Gold Before and During the COVID-19 Pandemic: A Comparative Analysis - Safinatuz Zuhriyah; Wisnu Panggah Setiyono; Detak Prapanca (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study aims to investigate empirical evidence of a comparison of investment instruments, including Bitcoin, Indonesia Composite Index (ICI), and gold, before and during the COVID-19 pandemic.Design/Methodology/Approach: Analytical methods employed comparison study using secondary data. The Microsoft Excel program was utilized to calculate formulas for each variable. Then, data were statistically processed using the SPSS application, i.e., independent sample test, testing for differences. The sample used in this study was the closing price of Bitcoin, the price of the ICI, and the price of gold, with monthly data from the beginning of January 2018 to the end of December 2021, to demonstrate a significant difference between the risks of Bitcoin, ICI, and gold before and during the COVID-19 pandemic.Research findings: The hypothesis test results revealed that before the COVID-19 pandemic, the investment risk of ICI and gold was the lowest, with a significance level of 0.000 (0.0000.05) on a different t-test at a 5% significance level. Thus, there was a significant difference in investment risk between ICI and gold. Meanwhile, during the COVID-19 pandemic, the risk of investing between Bitcoin and the ICI was the lowest, with a significance level of risk of was 0.000 (0.000 0.05) on different tests at the significance levels of 5%. In short, there was a big difference in investment risk between Bitcoin and the ICI.Theoretical contribution/Originality: This study provides additional literature on decision-making, especially on risk.